Aerogel material with nano defect MOF-801 loaded on surface of calcium alginate as well as preparation method and application of aerogel material
By loading nanodefective MOF-801 on the surface of calcium alginate and crosslinking with polypyrrole to form an aerogel, the problem of low water collection efficiency of MOFs under low humidity conditions is solved, efficient water absorption and photothermal conversion are achieved, and atmospheric collection is met Water efficient cleaning of water needs.
Patent Information
- Application Number
- CN202411187815.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
AI Technical Summary
The working capacity of existing MOFs when water collection is low under low humidity conditions, resulting in high energy consumption and low water yield, and it is necessary to improve water absorption efficiency and water stability through structural modification.
Aerogel material with surface loaded nanodefective MOF-801 of calcium alginate, combined with polypyrrole (PPy) as the photothermal conversion material, PPy/MOF-801-G/CA is formed through cross-linking and freeze-drying steps during the preparation process. Aerogel improves its water absorption performance and photothermal conversion efficiency.
It achieves high water absorption capacity and rapid desorption rate, and can collect clean water that meets WHO drinking water standards, significantly improving the efficiency and water quality of atmospheric water collection.
Smart Images

Figure CN119119564A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of atmospheric water collection, and in particular to an aerogel material with nano-defect MOF-801 loaded on the surface of calcium alginate, and a preparation method and application thereof. Background Art
[0002] Currently, the world is suffering from water shortage, and with the continuous increase in population and the increasing water pollution problem, the plight of water shortage is expected to worsen further. As a sustainable green technology, atmospheric water harvesting technology provides a promising sustainable solution to alleviate the pressure of global water shortage. Since the adsorption-based adsorptive atmospheric water harvesting (SAWH) technology is mainly based on water storage and then desorption through solar energy for collection, researchers are committed to finding smart and efficient adsorption materials.
[0003] Among many materials, metal organic frameworks (MOFs) with excellent porosity, high specific surface area, structural stability under exposure to water vapor within the working pressure range, and moderate regeneration temperature provide a feasible solution for water collection from air. Among various MOFs, MOF-801, which is cost-effective and water-stable, has been successfully used to collect water from low humidity. However, the low working capacity inevitably leads to high energy consumption and low water production rate. Therefore, it is necessary to make some appropriate modifications to MOFs to significantly improve their water absorption efficiency and water stability. The structural defects in the MOFs framework have a significant impact on its properties, so the adsorption and water collection capacity of MOF-801 can be improved by adjusting the defective structure. Hygroscopic porous polymers (HPPs) have been developed and reported, such as gels, gel derivatives, and sponge / foam modifications. Benefiting from their versatile adsorption mechanism and unique structural characteristics, HPPs have the advantages of high water absorption capacity and fast adsorption kinetics compared with powdered adsorbents. HPPs can play an ideal AWH performance in actual atmospheric water collection without sacrificing the performance of powdered materials. Summary of the invention
[0004] The present invention discloses a preparation method and application of an aerogel material of a calcium alginate surface loaded with nano-defect MOF-801, and aims to prepare an atmospheric water-collecting aerogel material with excellent water absorption performance and high photothermal conversion efficiency by using nano-defect MOF-801 loaded on the surface of a calcium alginate structure as a water-absorbing substrate and PPy as a photothermal conversion material. The photothermal aerogel material has excellent water absorption performance and a fast desorption rate, and can collect clean water that meets the WHO drinking water quality standards in practical applications.
[0005] The present invention adopts the following scheme to achieve the above purpose: A method for preparing an aerogel material with nano-defect MOF-801 loaded on the surface of calcium alginate, the method comprising the following steps: S1. adding zirconium oxychloride octahydrate to a mixed solution of formic acid and deionized water to form a homogeneous solution, then adding fumaric acid to the homogeneous solution, reacting at room temperature for a period of time, and then centrifuging, washing and drying the obtained product to obtain MOF-801-G; S2. Pyrrole monomer is added to deionized water and stirred for a period of time to form a homogeneous solution, and then ferric chloride hexahydrate solution is added dropwise to the homogeneous solution and stirred for a period of time, and the obtained product is repeatedly filtered and washed until the filtrate is colorless, and then dried to obtain polypyrrole (PPy) powder; S3. PPy and MOF-801-G powders were added to deionized water to form a suspension, sodium alginate was added to the uniformly dispersed suspension, and stirred at a preset temperature; S4. After cooling to room temperature, the above solution was poured into a mold and freeze-dried for a period of time to obtain PPy / MOF-801-G / SA (PMS) aerogel; S5. The PMS aerogel was immersed in a calcium chloride solution for cross-linking, and then freeze-dried after a period of cross-linking to obtain PPy / MOF-801-G / CA (PMC) aerogel.
[0006] Preferably, in step S1, the mass ratio of zirconium oxychloride octahydrate, formic acid, deionized water and fumaric acid is 3.50:80:20:1.75, the reaction time at room temperature is 48 hours, and the drying condition is drying at 70°C for 12 hours.
[0007] Preferably, in step S2, the concentrations of the pyrrole monomer solution and the ferric chloride hexahydrate solution are 3.6wt% and 14.06wt% respectively, the stirring time of the pyrrole monomer added to the deionized water is 30-40min, the stirring time after adding the ferric chloride hexahydrate solution is continued for 24h, and the drying condition is drying at 60°C for 24h.
[0008] Preferably, in step S3, the mass ratio of PPy, MOF-801-G, sodium alginate and deionized water is 0.5:0.25-2:1:98.25-96.5, and the preset temperature is 65°C.
[0009] Preferably, in step S4, the freeze-drying time is 24 hours.
[0010] Preferably, in step S5, the concentration of calcium chloride is 2 wt %, the cross-linking time is 12 h, and the freeze-drying time is 24 h.
[0011] The present invention also provides an aerogel material with nano-defect MOF-801 loaded on the surface of calcium alginate. The aerogel material is prepared based on the preparation method as described above.
[0012] The present invention further provides an application of the aerogel material as described above in the field of atmospheric water collection.
[0013] By adopting the above technical solution, the present invention can achieve the following technical effects: (1) By embedding the powdered desiccant into the aerogel-based skeleton, the present invention enables HPPs to exert ideal AWH performance in actual atmospheric water collection without sacrificing the performance of the powdered material.
[0014] (2) The calcium alginate-loaded nano-defect MOF-801 PMC aerogel of the present invention has excellent pore structure and mechanical properties, combined with the wide light absorption range of the PPy material, which enables it to have a higher photothermal conversion efficiency.
[0015] (3) The calcium alginate-loaded nano-defect MOF-801 PMC aerogel of the present invention exhibits excellent water absorption performance and rapid desorption rate. In addition, the PMC aerogel can collect clean water that meets the WHO drinking water quality standards in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 It is a characterization diagram of the water absorption performance of the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 of Examples 1, 2, 3 and 4 of the present invention; Figure 2 It is a characterization diagram of the desorption performance of the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 of Examples 1, 2, 3 and 4 of the present invention; Figure 3 is a pore size distribution diagram of the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 according to Example 2 of the present invention; Figure 4 This is a comparison chart of the water quality of water collected by the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 according to Example 2 of the present invention. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0019] First, zirconium oxychloride octahydrate, formic acid, deionized water and fumaric acid were stirred and mixed at a mass ratio of 3.50:80:20:1.75 at 600 rpm for 90 minutes, reacted at room temperature for 48 hours, and then the obtained product was centrifuged, washed with water and ethanol, and dried at 70°C for 12 hours to obtain MOF-801-G. 3.6 wt% of pyrrole monomer was added to deionized water and stirred for 30-40 minutes to form a homogeneous solution, and then 14.06 wt% of ferric chloride hexahydrate solution was added dropwise to the above homogeneous solution and continued to stir for 24 hours. The obtained product was repeatedly filtered and washed until the filtrate was colorless, and dried at 60°C for 24 hours to obtain polypyrrole (PPy) powder. The material was subsequently used to carry out the subsequent preparation process according to the process of Examples 1-4.
[0020] Example 1 The preparation method of a calcium alginate-loaded nano-defect MOF-801 PMC aerogel provided in this embodiment can be obtained by the following steps: (1) PPy and MOF-801-G powders were added to deionized water to form a suspension, sodium alginate was added to the uniformly dispersed suspension, and the mixture was stirred at 65°C. The mass ratio of PPy, MOF-801-G, sodium alginate and deionized water was 0.5:0.25:1:98.25.
[0021] (2) After cooling to room temperature, the above solution was poured into a mold and freeze-dried for 24 hours to obtain PPy / 0.25MOF-801-G / SA (P0.25MS) aerogel; (3) The PMS aerogel was immersed in a 2 wt% calcium chloride solution for cross-linking. After cross-linking for 12 h, it was freeze-dried for 24 h to obtain PPy / 0.25MOF-801-G / CA (P0.25MC) aerogel.
[0022] Example 2 The preparation method of a calcium alginate-loaded nano-defect MOF-801 PMC aerogel provided in this embodiment can be obtained by the following steps: (1) PPy and MOF-801-G powders were added to deionized water to form a suspension, sodium alginate was added to the uniformly dispersed suspension, and the mixture was stirred at 65°C. The mass ratio of PPy, MOF-801-G, sodium alginate and deionized water was 0.5:0.5:1:98.25.
[0023] (2) After cooling to room temperature, the above solution was poured into a mold and freeze-dried for 24 hours to obtain PPy / 0.5MOF-801-G / SA (P0.5MS) aerogel; (3) The PMS aerogel was immersed in a 2 wt% calcium chloride solution for cross-linking. After cross-linking for 12 h, it was freeze-dried for 24 h to obtain PPy / 0.5MOF-801-G / CA (P0.5MC) aerogel.
[0024] Example 3 The preparation method of a calcium alginate-loaded nano-defect MOF-801 PMC aerogel provided in this embodiment can be obtained by the following steps: (1) PPy and MOF-801-G powders were added to deionized water to form a suspension, sodium alginate was added to the uniformly dispersed suspension, and the mixture was stirred at 65°C. The mass ratio of PPy, MOF-801-G, sodium alginate and deionized water was 0.5:1:1:98.25.
[0025] (2) After cooling to room temperature, the above solution was poured into a mold and freeze-dried for 24 hours to obtain PPy / 1MOF-801-G / SA (P1MS) aerogel; (3) The PMS aerogel was immersed in a 2 wt% calcium chloride solution for cross-linking. After cross-linking for 12 h, it was freeze-dried for 24 h to obtain PPy / 1MOF-801-G / CA (P1MC) aerogel.
[0026] Example 4 The preparation method of a calcium alginate-loaded nano-defect MOF-801 PMC aerogel provided in this embodiment can be obtained by the following steps: (1) PPy and MOF-801-G powders were added to deionized water to form a suspension, sodium alginate was added to the uniformly dispersed suspension, and the mixture was stirred at 65°C. The mass ratio of PPy, MOF-801-G, sodium alginate and deionized water was 0.5:2:1:98.25.
[0027] (2) After cooling to room temperature, the above solution was poured into a mold and freeze-dried for 24 hours to obtain PPy / 2MOF-801-G / SA (P2MS) aerogel; (3) The PMS aerogel was immersed in a 2 wt% calcium chloride solution for cross-linking. After cross-linking for 12 h, it was freeze-dried for 24 h to obtain PPy / 2MOF-801-G / CA (P2MC) aerogel.
[0028] Test Example 1 A homemade constant temperature and humidity chamber was used to simulate different relative humidity environments for indoor water vapor adsorption test, and the water vapor absorption of the aerogel materials provided in different embodiments was compared to determine the difference in their water absorption performance. The indoor water vapor adsorption test simulated different relative humidity environments by a homemade constant temperature and humidity chamber, and the relative humidity environment was 10-95%RH and the temperature was 5-45°C. Before the test, the PMC aerogel was placed at 80°C and dried for 6 hours to completely remove the moisture inside the aerogel material. After the environment in the constant temperature and humidity chamber stabilized at 25°C and 60%RH, the PMC aerogel was placed in a constant temperature and humidity chamber for indoor water vapor adsorption test. An electronic mass balance (AX224ZH / E, OHAUS) was used to track the mass changes of the PMC aerogel within 12 hours.
[0029] from Figure 1 It can be seen that the water absorption capacity of the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 in Example 2 can reach 1.106 gg -1 , and its water absorption capacity is higher than that of the materials provided in other embodiments.
[0030] Test Example 2 The desorption test was conducted by simulating sunlight with an indoor xenon lamp, and the desorption rates of the aerogel materials provided in different embodiments were compared to determine the differences in their photothermal performance. The desorption test was simulated by Perfectlight (PLS-SXE300+), and the simulated solar flux was 500 to 2000 W m 2 The spectrum was calibrated using a standard AM 1.5G filter. Before testing, the light intensity was always calibrated using an automatic optical power meter (Aulight, CEL-NP2000-2(10)A). The PMC aerogel sample was placed under light. An electronic mass balance was used to track the weight loss of the entire device. The desorption process was measured for 2 h in a simulated sunlight environment with an ambient temperature of 25 °C and a relative humidity of 60%.
[0031] from Figure 2It can be seen that the desorption rate of the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 in Example 2 can reach 99.19%, which is higher than the materials provided in other examples.
[0032] Test Example 3 The pore structure of the calcium alginate-loaded nano-defect MOF-801 PMC aerogel provided in Example 2 was analyzed using a scanning electron microscope and an automatic specific surface area and porosity analyzer. Figure 3 The specific surface area and pore size distribution of aerogels were measured by automatic specific surface area and porosity analyzer. Figure 3 It can be seen that the aerogel has a porous structure, and MOF-801-G and PPy are loaded on its calcium alginate surface. The synergistic effect between them can promote the adsorption and desorption of water vapor.
[0033] Test Example 4 The PMC aerogel with calcium alginate loaded with nano-defect MOF-801 prepared in Example 2 was used to construct a water vapor adsorption and desorption process in a homemade outdoor water collection device. The PMC aerogel water vapor adsorption test was carried out for 12 hours at night and irradiated during the day. The generated vapor condensed into liquid and reached the recovery container, and then the ion concentration in the collected water was detected by inductively coupled plasma mass spectrometry.
[0034] from Figure 4 It can be seen that the Na in the water collected by the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 in Example 2 in the outdoor water collection test + , K + Mg 2+ , Ca 2+ and Al 3+ The ion concentration meets the drinking water standard of the World Health Organization, proving that the PMC aerogel of calcium alginate loaded with nano-defect MOF-801 can be well applied in the field of atmospheric water collection.
[0035] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing an aerogel material of calcium alginate surface loaded with nano-defect MOF-801, It is characterized in that The method comprises the following steps: S1. adding zirconium oxychloride octahydrate to a mixed solution of formic acid and deionized water to form a homogeneous solution, then adding fumaric acid to the homogeneous solution, reacting at room temperature for a period of time, and then centrifuging, washing and drying the obtained product to obtain MOF-801-G; S2. Pyrrole monomer is added to deionized water and stirred for a period of time to form a homogeneous solution, and then ferric chloride hexahydrate solution is added dropwise to the homogeneous solution and stirred for a period of time, and the obtained product is repeatedly filtered and washed until the filtrate is colorless, and then dried to obtain polypyrrole (PPy) powder; S3. PPy and MOF-801-G powders were added to deionized water to form a suspension, sodium alginate was added to the uniformly dispersed suspension, and stirred at a preset temperature; S4. After cooling to room temperature, the above solution was poured into a mold and freeze-dried for a period of time to obtain PPy / MOF-801-G / SA (PMS) aerogel; S5. The PMS aerogel was immersed in a calcium chloride solution for cross-linking, and then freeze-dried after a period of cross-linking to obtain PPy / MOF-801-G / CA (PMC) aerogel.
2. A method for preparing an aerogel material of calcium alginate surface loaded with nano-defect MOF-801 according to claim 1, It is characterized in that In step S1, the mass ratio of zirconium oxychloride octahydrate, formic acid, deionized water and fumaric acid is 3.50:80:20:1.75, the reaction time at room temperature is 48 hours, and the drying condition is drying at 70° C. for 12 hours.
3. The method for preparing an aerogel material of calcium alginate surface loaded with nano-defect MOF-801 according to claim 1, It is characterized in that In step S2, the concentrations of the pyrrole monomer solution and the ferric chloride hexahydrate solution are 3.6wt% and 14.06wt%, respectively. The stirring time of the pyrrole monomer added to the deionized water is 30-40min, and the stirring time after adding the ferric chloride hexahydrate solution is continued for 24h. The drying condition is drying at 60°C for 24h.
4. The method for preparing an aerogel material of calcium alginate surface loaded with nano-defect MOF-801 according to claim 1, It is characterized in that In step S3, the mass ratio of PPy, MOF-801-G, sodium alginate and deionized water is 0.5:0.25~2:1:98.25~96.5, and the preset temperature is 65°C.
5. The method for preparing an aerogel material of calcium alginate surface loaded with nano-defect MOF-801 according to claim 1, It is characterized in that In step S4, the freeze-drying time is 24 hours.
6. The method for preparing an aerogel material of calcium alginate surface loaded with nano-defect MOF-801 according to claim 1, It is characterized in that In step S5, the concentration of calcium chloride is 2 wt %, the cross-linking time is 12 h, and the freeze-drying time is 24 h.
7. An aerogel material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the aerogel material as claimed in claim 7 in the field of atmospheric water collection.
Citation Information
Cited By
High-flame-retardant low-smoke halogen-free cable sheath material and preparation method thereof
CN121699271A
